Peraturan Yang Ditetapkan oleh Kepala Desa (Kajian Terhadap Pasal 8 ayat (1) UU No 12 Tahun 2011 Tentang Pembentukan Peraturan Perundang-Undangan) - Andress.D. Bakarbessy (Faculty of Law Hang Tuah University, 2017)
Article 2 Domestic Ministerial Regulation Number 111 of 2014 concerning technical guidelines for Village Regulations states that Type of Regulation in the village includes: a. Village Regulation b. Joint Regulation of the Village Head; and c. Village Head Regulation. Meanwhile, Article 8 paragraph (1) of the Law Establishing Legislation states that the type of legislation also includes the rules set by ... Village Heads or the equivalent. Based on the construction of norms Article 8 paragraph (1) of the Law on Establishment of Legislation, village regulations cannot be categorized as regulations established by the village head because a village regulation must have a joint agreement between the village head and the village consultative body and must be promulgated in Village and legal sheets become village regulations even though they are not stipulated by the village head.